"At least I tried, God damnit" and "Even a drop in the ocean is still more than nothing": In their own words, what motivates people to work in P/CVE?. Issue 4 (2nd October 2022) - Schlegel, Linda
ABSTRACT: The P/CVE sector is a growing and increasingly professionalised field in many countries affected by "homegrown" extremism. While opinions of individuals working and researching in the P/CVE sector have informed many studies, little is known about these professionals as people. This is problematic, because P/CVE employees are not black boxes; they have personal motivations, opinions, and experiences, which potentially influence their work and therefore the development and implementation of prevention and counter-extremism efforts. The present study offers a preliminary glimpse into P/CVE professionals as individuals by reporting the analysis of 27 experts interviews with academics and practitioners working in P/CVE, who describe their personal motivation for working in this particular field. These motivational factors range from childhood experiences to personal interest in the topic, anger, the wish for a positive personal impact, the desire to use research to improve social ills, and personalised responsibility to protect democracy